Analysis of The Use of Behaviorism Theory in Physical Education Learning on Student Discipline in Elementary Schools - Nurfitri, Fadya; Suhenda Putra, Muhammad Arfrizal; An Naba, Qory Maryam; Hikam, Raihan Aslamul; Fauji, Rijal Ahmad (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyse the application of behaviourism theory in physical education (PE) learning to improve student discipline in elementary schools. The qualitative research method with a case study approach involved in-depth interviews with three PE teachers from elementary schools in Sumedang. Data were collected through interviews and documentation and then analyzed using triangulation techniques to ensure the validity of the research results. The results showed that the application of behaviourism theory, through positive reinforcement such as praise and rewards, as well as negative reinforcement such as educational reprimands, was able to improve student discipline. These strategies include routine activities such as line setting, collective prayer, and warm-ups that help students understand the importance of order. Adaptive approaches, such as tailoring learning methods to students' interests, were also found to be effective in improving discipline. This study concludes that the application of behaviourism theory in PE learning not only improves student discipline but also creates a conducive learning environment. Appropriate behaviour reinforcement strategies can help students develop disciplinary habits and other positive characteristics early on.